Non-steroid, non-antibiotic anti-biofilm therapy for the treatment of chronic rhinosinusitis: a systematic review. Issue 3 (5th March 2021) - Taylor, A; Fuzi, J; Sideris, A; Banks, C; Havas, T E
Abstract: Objective: Chronic rhinosinusitis patients with biofilms cultured from their sinonasal cavity have greater symptom burden and risk of recalcitrant disease. A number of non-antibiotic, 'anti-biofilm' treatments exist which show anti-biofilm properties in preclinical studies. There is little evidence evaluating their impact on clinical symptom scores in chronic rhinosinusitis. Method: A systematic review was performed to assess the literature regarding the efficacy of non-steroid, non-antibiotic, anti-biofilm specific topical therapies in the treatment of chronic rhinosinusitis. The primary outcome assessed was change in validated patient reported outcome measures before and after anti-biofilm treatment. Results: Thirteen studies assessing the effect of anti-biofilm therapies in chronic rhinosinusitis through validated patient-reported outcome measures were included. Seven different anti-biofilm specific therapies for chronic rhinosinusitis were identified. None of the seven anti-biofilm therapies was identified as being confidently efficacious beyond placebo. Only one therapy (intranasal xylitol) showed a statistically significant reduction in symptom scores compared with placebo in more than one trial. Conclusion: Robust evidence supporting the use of various anti-biofilm therapies in chronic rhinosinusitis is lacking. Further high quality, human, in vivo trials studying the effect of anti-biofilm therapies in chronic rhinosinusitis are needed to address the deficiencies of the current evidence base.